CHANGE OF CULTURE AND MINSET OF LUMBANG COMMUNITY AFTER ATTENDANCE SMK NEGERI 1 LUMBANG PROBOLINGGO DISTRICTS, EAST JAVA - Yanny Ariska (Fakultas Ilmu Politik dan Ilmu Sosial, Universitas Brawijaya, 2019)
The mindset of the people is influenced by the culture of the surrounding environment which has been affecting the daily life. Educational institutions become a means of individual development to develop outside the family. The Lumbang community must be willing to go to school far from their area due to the lack of educational institutions. Since 2016, the attendance of SMK Negeri 1 Lumbang has brought a change in culture and mindset in society. The community had a culture of early marriage, divorce, child labor, and unemployment at a young age, now this is no longer the case. The community experienced a change in culture and mindset after the opportunity at the SMK level.